(untitled) (Global Journal of Science Frontier Research, 2015)
The study focused on the effects of migration by nomadic farmers on livelihoods of the rural crop famers in Enugu State of Nigeria. The study had the following specific objectives; determine the socio-economic attributes of the rural crop and nomadic farmers; identify the sources of nomadic farmers conflicts in the rural crop farmers farm fields; assess the socioeconomic effects of migration by nomadic farmer on rural development and describe the methods adopted to resolve nomadic farmers conflicts with rural crop famers in the area. In the sampling procedure, purposive and random sampling techniques were used. A purposive multi stage sampling technique was used to obtain a sample size of 60 nomadic farmers and 80 rural farmers, information was elicited using questionnaires.